MOLECULAR PHYLOGENETIC ANALYZE OF FUSARIUM FROM AGARWOOD AND OTHERS FUSARIUM WITH DIFFERENT TYPE OF NUTRITION BASED ON GEN ITS 1 - I Gde Adi Suryawan Wangiyana (JURNAL SANGKAREANG MATARAM, 2016)
Fusarium is a common mold used as inoculants for inducing resin formation in agarwood tree. Molecular phylogenetic analyze is important to be done to determine the correlation between type of nutrition of Fusarium and its ability to associated with Agarwood. ITS 1 gene sequences were downloaded from NCBI gene bank was used as sequences to reconstruct phylogenetic tree. ClustalX 2.1 program were used for multiple alignment of sequences. Two phylogenetic tree, Neighbor Joining and Maximum Likelihood, were reconstructed with MEGA 5.1 program. One phylogenetic tree were reconstructed with mrbayes program using Markov Chain Monte Carlo method. Phydit program were used to construct similarity matrix between sequences.Different type of nutrition on Fusarium including: endophytic, saprophytic and phytopathogenic were not a monophyletic based on phylogenetic tree analyze. That type of nutrition was formed by adaptation process. They do not share that characteristic withtheir common ancestor. Fusarium from agarwood has the same clade with phytopathogenic Fusarium in all phylogenetic trees. They also have the highest ITS 1 gene sequence similarity with phytopathogenic Fusarium. Therefore, it could be concluded that Fusarium from agarwood are phytopathogenic group and they have pathogen-host association with agarwood.